2019
DOI: 10.4183/aeb.2019.544
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Revisited in 2020

Abstract: Calcitonin (CT) is a polypeptidic hormone specifically secreted by the thyroid parafollicular cells (C cells) and tangentially involved in human phosphocalcic and bone metabolism. CT from other species (e.g. salmon) is more potent than human CT and has limited therapeutic applications. The neoplastic proliferation of C cells leads to medullary thyroid carcinoma (MTC) generally characterized by an increase of CT secretion. Serum CT is therefore the ideal marker for MTC and can confirm its presence at an early s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
0
10
0
5
Order By: Relevance
“…Although the detection of MTC through routine calcitonin screening has recently been shown to lead to early stage diagnosis, the American Thyroid Association (ATA) guideline did not make recommendations for routine calcitonin measurement in nodular thyroid patients, leaving the decision up to the clinicians (13). However, many authorities recommend routine serum calcitonin measurement in nodular thyroid disease (4,9,10,17,19,20), but this recommendation is very controversial since it is considered that thyroid nodule prevalence is 33-68% (6,(21)(22)(23). In addition, the prevalence of MTC in nodular thyroid disease is unknown, and in thyroid cancers, its prevalence has been found to be 1-2% (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the detection of MTC through routine calcitonin screening has recently been shown to lead to early stage diagnosis, the American Thyroid Association (ATA) guideline did not make recommendations for routine calcitonin measurement in nodular thyroid patients, leaving the decision up to the clinicians (13). However, many authorities recommend routine serum calcitonin measurement in nodular thyroid disease (4,9,10,17,19,20), but this recommendation is very controversial since it is considered that thyroid nodule prevalence is 33-68% (6,(21)(22)(23). In addition, the prevalence of MTC in nodular thyroid disease is unknown, and in thyroid cancers, its prevalence has been found to be 1-2% (1).…”
Section: Discussionmentioning
confidence: 99%
“…The production of calcitonin, a 32 amino acid long polypeptide hormone, is a characteristic feature of this tumor. Therefore, calcitonin measurement plays an important role in both diagnosis and follow-up of MTC patients (5,6) Many studies have shown that routine measurement of serum calcitonin may lead to earlier detection of MTC in patients with thyroid nodules (4,(7)(8)(9)(10)(11)(12). The American Thyroid Association (ATA) has remained neutral on the subject of routine calcitonin measurement in thyroid nodule follow-up, leaving the decision up to the clinicians (13).…”
Section: Introductionmentioning
confidence: 99%
“…The serum Ctn level is generally proportional to tumor involvement, and lower than expected readings should raise suspicion for factors affecting the laboratory assay. In general, values <10 pg/mL are reassuring for no C-cell disease, 10-100 pg/mL indeterminate, 100-500 pg/mL Ccell hyperplasia or early MTC, 500-1,000 pg/mL with metastatic disease, and greater than 1,000 pg/L for distant metastasis (Table 3) [15,25].…”
Section: Serum Calcitoninmentioning
confidence: 99%
“…Estas hormonas sexuales tienen una función de evitar la osteoclastogénesis, inhibir el proceso de apoptosis de osteoblastos y osteocitos, y evitar la formación de osteoclastos, lo que regula positivamente la OPG en la vía de señalización celular RANK/OPG (Figura 3) (46) . La calcitonina es una hormona secretada por las células parafoliculares de la glándula tiroides (48) , en respuesta al aumento de calcio sérico (49) . Esta hormona actuaría al disminuir la reabsorción de calcio en el riñón (19) y al inhibir la formación ósea a través de la reducción en la liberación de la esfingosina-1-fosfato (SP1) por los osteoclastos (50) .…”
Section: Factores Genéticos Y Hormonales Como Determinantes De La Masa óSeaunclassified